AGRIBUSINESS PRODUCT DIFFERENTIATION AND BRANDING STRATEGY TO INCREASE COMPETITIVENESS IN THE GLOBAL MARKET - Desi Novita (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Competition in the global agribusiness industry is increasingly fierce, requiring business actors to implement effective strategies to increase competitiveness. Differentiation and branding are two main strategies that can provide added value and differentiate agribusiness products from competitors. This research aims to analyze the role of differentiation and branding strategies in increasing the competitiveness of agribusiness products in the global market through a literature review. The method used in this research is a systematic literature review (SLR) by analyzing various scientific sources, including academic journals, books, industry reports and official publications. The study results show that differentiation strategies, which include product innovation, quality certification, sustainability and production technology, play an important role in creating competitive advantage. On the other hand, strong branding helps build brand equity, increase customer loyalty, and strengthen the product's position in the international market. The combination of differentiation and branding has been proven to contribute to increasing exports and global market penetration. The implications of this research show that agribusiness industry players need to integrate product innovation with effective branding strategies and utilize digital technology for global marketing. With the right approach, agribusiness products can have a sustainable competitive advantage and be able to compete in international markets.